Disputed Territory: Land Struggle in the Valley of Sixaola, Costa Rica (1960-1990) - Llaguno Thomas, José Julián (2012)
The following paper explores the process of struggle for land in the valley of Sixaola using different written and oral sources. This case seeks to reflect the impact that this conflict had in the recreation of the peasantry as a political subject and the transformation of social relations that allowed the development of a community. With this, we capture some reflections from a process of linking several years with the local population and put in debate the prospects for a town that has been forgotten by the academic literature and a window that allows entry to a more complex problems on the land struggles in Costa Rica.